Analysis of the influence parameters on steel strip defects in continuous roll casting-rolling - Alexey Nogovitsyn; Olha Kholiavik; Ruslan Boris; Dmytro Sokhan; Natalia Seminska (Mechanics and Advanced Technologies)
Problem. The casting-rolling process is currently one of the most effective and promising processes used for the production of steel sheets. The advantages of this process include the small dimensions of the unit and a significant reduction in energy resources. This occurs due to a combination of technological operations and absence of the intermediate heating of the metal. At the same time, there is the challenge of a sustainable industrial process for producing high quality steel sheets. Objective. Companies developing direct melt strip processes using twin-roll crystallizers report a number of challenges they face. Among such problems are defects on the surface of the cast strip. Currently, there is no generally accepted classification of surface defects, such as surface cracks, wrinkles, namely, depressions, and transverse deformation bands. At the moment, there is also no justification for the reasons for the appearance of surface defects during the rolling process. Implementation methodology. Based on the research results, a hypothesis was proposed about the causes of defects on the surface of the cast strip and ways to prevent them. During the operation of two-roll crystallizers, a combination of metal hardening processes and its subsequent plastic deformation occurs. The metal moves sequentially through areas of crystallization and deformation. During the research, the authors calculated the process of roll casting-rolling. Conclusions. Based on the research results, we believe that when casting steel using twin-roll casting-rolling, it is necessary to reduce the compression to a minimum value. This recommendation will ensure welding of defects on the surface. The use of this proposal will allow the casting process to be carried out at high speed and little force to be applied to squeeze the rolls. We propose to carry out the process of forming a cast strip with the necessary quality parameters at the following stages of rolling.